Klippel-Feil syndrome with upper cervical intradural arachnoid cyst - Akgun, Bekir; Kaplan, Metin; Yildirim, Hanefi (Georg Thieme Verlag Kg, 2008)
Klippel-Feil syndrome can be seen with bony anomalies of the craniocervical junction and syringomyelia. However, association of Klippel-Feil syndrome with upper cervical arachnoid cyst has not been reported previously. This report demonstrates clinical and radiological features of a case of Klippel-Feil syndrome complicated by Chiari I malformation, upper cervical arachnoid cyst and syringomyelia. A 7-year-old girl was evaluated due to headache, neck pain and restricted cervical movements. Craniocervical evaluation of the case demonstrated Chiari I malformation, partial fusion defect at C2-C3, C5-C6 vertebrae, upper cervical arachnoid cyst and cervicothoracal syringomyelia. Suboccipital craniectomy, C1 laminectomy, arachnoid cyst excision, and duraplasty with autologous fascia lata were performed. The headache and the neck pain of the patient improved after the operation. The arachnoid cyst did not recur.
Keywords: Chiari malformation type I; Klippel-Feil syndrome; syringomyelia; upper cervical arachnoid cyst